PENGARUH KUALITAS JASA, INOVASI PRODUK DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN PADA PT APPLE PRIMA PERSADA - Ng, viviany; Evyanto, Winda (LPPM Universitas Putera Batam, 2021)
At present, developments in science and technology have been very advanced. So that the need for fast information and communication globally has encouraged competitive competition between companies in an effort to dominate the market to meet customer satisfaction. This study aims to determine the effect of service quality, product innovation and brand image on customer satisfaction at PT Apple Prima Persada. PT Apple Prima Persada is a company engaged in printing located in the city of Batam, Riau Islands. The analytical tool used is multiple linear regression analysis and the sample used was 146 respondents using simple random sampling and with the tools using the SPSS program version 25. The data collection was done by distributing questionnaires that have been tested for validity and reliability. The results show that service quality, product innovation and brand image have a positive and significant effect on customer satisfaction at PT Apple Prima Persada.